Ð’Ð¾Ð·Ñ€Ð°ÑÑ‚Ð½Ñ‹Ðµ Ð¾ÑÐ¾Ð±ÐµÐ½Ð½Ð¾ÑÑ‚Ð¸ Ñ€Ð¾Ð»Ð¸ Ð¾ÐºÑÐ¸Ð´Ð° Ð°Ð·Ð¾Ñ‚Ð° Ð² Ð¼ÐµÑ…Ð°Ð½Ð¸Ð·Ð¼Ð°Ñ… Ð°Ð´Ð°Ð¿Ñ‚Ð°Ñ†Ð¸Ð¸ Ð¶Ð¸Ð²Ð¾Ñ‚Ð½Ñ‹Ñ… Ðº Ñ€Ð¸Ñ‚Ð¼Ð¸Ñ‡ÐµÑÐºÐ¸Ð¼ Ñ…Ð¾Ð»Ð¾Ð´Ð¾Ð²Ñ‹Ð¼ Ð²Ð¾Ð·Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸ÑÐ¼. Ð¡Ð¾Ð¾Ð±Ñ‰ÐµÐ½Ð¸Ðµ I. Ð¡Ð¾Ð´ÐµÑ€Ð¶Ð°Ð½Ð¸Ðµ ÐºÐ¾Ð½ÐµÑ‡Ð½Ñ‹Ñ… Ð¿Ñ€Ð¾Ð´ÑƒÐºÑ‚Ð¾Ð² Ð¾Ð±Ð¼ÐµÐ½Ð° NO Ð² ÑÑ‹Ð²Ð¾Ñ€Ð¾Ñ‚ÐºÐµ ÐºÑ€Ð¾Ð²Ð¸ Ð¸ Ð¼Ð¸Ð¾ÐºÐ°Ñ€Ð´Ðµ Ð¼Ð¾Ð»Ð¾Ð´Ñ‹Ñ… Ð¸ ÑÑ‚Ð°Ñ€Ñ‹Ñ… Ð¶Ð¸Ð²Ð¾Ñ‚Ð½Ñ‹Ñ… Ð¿Ð¾ÑÐ»Ðµ Ñ€Ð¸Ñ‚Ð¼Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… Ñ…Ð¾Ð»Ð¾Ð´Ð¾Ð²Ñ‹Ñ… Ð²Ð¾Ð·Ð´ÐµÐ¹ÑÑ‚ - Babijchuk, V. G. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
Influence of rhythmical cold effects (â€“120Â°C) on content of final products of nitrogen oxide (NO) exchange in blood serum and myocardium of young and aged rats has been studied. NO activity is supposed to play a role of pathogenic regulatory factor, whose activity is reduced in aged rats. The rise in the content of NO exchange final products in blood serum after 6 sessions of extreme cryoeffects in young rats and after 6-9 sessions in aged ones has been noted. The reduction of the content of nitrites in myocardium of rats can indicate an NO intensive expenditure by myocardial cells. The similar effect for aged rats in the dynamics of experiment is â€œdelayedâ€, that is related to a decline in adaptive possibilities of ageing organism.